Overhauser effects in insulating solids - Can, T. V. (American Institute of Physics, 2014)
We report magic angle spinning, dynamic nuclear polarization (DNP) experiments at magnetic fields of 9.4 T, 14.1 T, and 18.8 T using the narrow line polarizing agents 1,3-bisdiphenylene-2-phenylallyl (BDPA) dispersed in polystyrene, and sulfonated-BDPA (SA-BDPA) and trityl OX063 in glassy glycerol/water matrices. The (1)H DNP enhancement field profiles of the BDPA radicals exhibit a significant DNP Overhauser effect (OE) as well as a solid effect (SE) despite the fact that these samples are insulating solids. In contrast, trityl exhibits only a SE enhancement. Data suggest that the appearance of the OE is due to rather strong electron-nuclear hyperfine couplings present in BDPA and SA-BDPA, which are absent in trityl and perdeuterated BDPA (d(21)-BDPA). In addition, and in contrast to other DNP mechanisms such as the solid effect or cross effect, the experimental data suggest that the OE in non-conducting solids scales favorably with magnetic field, increasing in magnitude in going from 5 T, to 9.4 T, to 14.1 T, and to 18.8 T. Simulations using a model two spin system consisting of an electron hyperfine coupled to a (1)H reproduce the essential features of the field profiles and indicate that the OE in these samples originates from the zero and double quantum cross relaxation induced by fluctuating hyperfine interactions between the intramolecular delocalized unpaired electrons and their neighboring nuclei, and that the size of these hyperfine couplings is crucial to the magnitude of the enhancements. Microwave power dependent studies show that the OE saturates at considerably lower power levels than the solid effect in the same samples. Our results provide new insights into the mechanism of the Overhauser effect, and also provide a new approach to perform DNP experiments in chemical, biophysical, and physical systems at high magnetic fields.